PERSONNEL POTENTIAL DEVELOPMENT IN THE 310TH MILITARY DISTRICT UNIT, MUEANG DISTRICT, TAK PROVINCE - Prasongtakun, Tadsapon; Srisatanon , Pornpana; Phongpaew, Aniruth; Kasemwutthichai , Winai (Journal of MCU Phetchaburi Review, 2026)
This research has the following objectives: 1) to study supporting factors, and personnel potential development in the 310th Military District Unit, Mueang District, Tak Province; 2) to compare personnel potential development in the 310th Military District Unit, categorized by personnel characteristics; 3) to study supporting factors that affect personnel potential development in the 310th Military District Unit. The sample group consisted of 250 personnel in the 310th Army Region Unit. The data collection instrument was a questionnaire. Statistical methods used for data analysis included mean, standard deviation, t-test, one-way ANOVA, and multiple regression analysis.The research findings revealed that: (1) Supporting factors overall and in each aspect were at the highest level, and personnel potential development in the 310th Military District Unit was at a high level overall. (2) Service users with different ages, education levels, and positions/ranks had significantly different potential development in the 310th Military District Unit. (3) Supporting factors in the areas of needs, knowledge, and development process significantly affected personnel potential development in the 310th Military District Unit at the .05 significance level.